2013
DOI: 10.3855/jidc.3127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of extended spectrum beta-lactamase-producing Enterobacter cloacae strains in Algeria

Abstract: Introduction: Expended spectrum β-lactamase (ESBL)-producing Enterobacter cloacae is an important nosocomial pathogen. In this study, the prevalence and the molecular epidemiology of ESBL producing E. cloacae strains isolated from various hospitals in Annaba, Algeria were investigated. Methodology: The study involved 63 isolates of E. cloacae obtained during 2009 at the four hospitals in Annaba. The detection of ESBL was performed using the double-disk synergy test and the combined disk test. Minimum inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
2
5
3
Order By: Relevance
“…In the present study, β -lactamase-producing bacteria were commonly found in ICU and surgical departments. This finding is similar to that reported in the eastern region of Saudi Arabia [20] and many parts of the world, such as in Algeria [21] and Nigeria [22]. It has been suggested that the higher use of invasive devices and the selective pressure of newer β -lactams for patients at ICU and surgery unit result in the emergence of such pathogens [20].…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, β -lactamase-producing bacteria were commonly found in ICU and surgical departments. This finding is similar to that reported in the eastern region of Saudi Arabia [20] and many parts of the world, such as in Algeria [21] and Nigeria [22]. It has been suggested that the higher use of invasive devices and the selective pressure of newer β -lactams for patients at ICU and surgery unit result in the emergence of such pathogens [20].…”
Section: Discussionsupporting
confidence: 86%
“…However, the current result was higher than of the study findings reported from Jima Ethiopia (51%) [17] and of study conducted in Algeria (47.6%) [18] and lower than reported from a tertiary care hospital in Riyadh capital Saudi Arabia (72%) [19]. These indicate that the distribution of ESBL producing organisms vary from region to region and may be higher in certain geographic areas [20].…”
Section: Bacterial Strainscontrasting
confidence: 85%
“…For instance, in 2008 cefuroxime resistance was 87.3%, cefotaxime 59%, aztreonam 33.3%, and ceftazidime 12.8% [ 95 ]. Isolates expressing various ESBLs were tested using a dual-disk potentiation method, which showed increased ESBL rates from 17.7% to 47.6% during the study period [ 95 , 96 , 97 ]. Additionally, based on the molecular analysis, it was observed that in 2009, bla SHV was 10% [ 96 ], bla TEM 19.9% to 70% [ 95 , 96 , 98 ], bla CTX-M 19.9% to 100% [ 95 , 96 , 97 , 98 ], and in 2013 bla VIM was 82.3% [ 99 ].…”
Section: Resultsmentioning
confidence: 99%